Zivilprozessuale Klärung von Grundsatzfragen im deutschen und französischen Recht - Weber, Sophia (Nomos Verlagsgesellschaft mbH & Co. KG, 2024)
The work deals with the prevention of principle decisions in civil procedure under German and French law. It deals with the legal policy question of how it can be ensured that the BGH, as a court of appeal in civil matters, can better fulfill its task of clarifying questions of principle (§ 543 para. 2 no. 1 ZPO) without being prevented from doing so by the exercise of party disposition powers. For this purpose, the study examines, among other things, the French Recours dans l'intérêt de la loi and the Saisine pour avis, and analyzes whether and, if so, how a comparable legal remedy could be implemented in Germany.